The perceived usefulness of different designs of the e-magazine - Shiratuddin, Norshuhada; Hussain, Hashiroh (Malaysian Educational Technology Association (META), 2005)
The electronic magazine (e-magazine) is a digitised magazine and an alternative source of reading materials for students. In order to introduce this source of complementary materials, the design features of the magazine have to be identified and their perceived usefulness elucidated. In this study, an approach was undertaken to collect students’ design requirements. The perceived usefulness was measured for two different designs, namely, the exact printed appearance and the multimedia enhanced design. The results indicate that the multimedia-enhanced version appears to be more useful compared to the exact printed appearance.